Metallation State of Human Manganese Superoxide Dismutase Expressed in Saccharomyces cerevisiae - Whittaker, Mei M. (2012)
Human manganese superoxide dismutase (Sod2p) has been expressed in yeast and the protein purified from isolated yeast mitochondria, yielding both the metallated protein and the less stable apoprotein in a single chromatographic step. At 30 °C growth temperature, more than half of the purified enzyme is apoprotein that can be fully activated following reconstitution, while the remainder contains a mixture of manganese and iron. In contrast, only fully metallated enzyme was isolated from a similarly constructed yeast strain expressing the homologous yeast manganese superoxide dismutase. Both the manganese content and superoxide dismutase activity of the recombinant human enzyme increased with increasing growth temperatures. The dependence of in vivo metallation state on growth temperature resembles the in vitro thermal activation behavior of human manganese superoxide dismutase observed in previous studies. Partially metallated human superoxide dismutase is fully active in protecting yeast against superoxide stress produced by addition of paraquat to the growth medium. However, a splice variant of human manganese superoxide dismutase (isoform B) is expressed as insoluble protein in both Escherichia coli and yeast mitochondria and did not protect yeast against superoxide stress.